2021
DOI: 10.1186/s13075-021-02515-w
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and prognosis of patients with isolated thrombotic vs. obstetric antiphospholipid syndrome: a prospective cohort study

Abstract: Background Several studies suggested that thrombotic and obstetric antiphospholipid syndromes could be independent identities, but few have systematically compared their clinical characteristics and prognosis. Objective The objective of this study is to identify key differences between thrombotic APS (tAPS) and obstetric APS (oAPS). Methods This single-center, prospective study included consecutive pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…1,5,20,27 On the contrary, hyperhomocysteinemia and antiphospholipid antibodies are accepted as risk factors for AT. 20,[27][28][29][30] However, there were rarely studies that attempted to support this hypothesis. Some studies have shown the prevalence of AT in people with PC, PS, and ATIII deficiencies, as well as other studies that had provided data on PC, PS, and AT III deficiency in patients with AT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,5,20,27 On the contrary, hyperhomocysteinemia and antiphospholipid antibodies are accepted as risk factors for AT. 20,[27][28][29][30] However, there were rarely studies that attempted to support this hypothesis. Some studies have shown the prevalence of AT in people with PC, PS, and ATIII deficiencies, as well as other studies that had provided data on PC, PS, and AT III deficiency in patients with AT.…”
Section: Discussionmentioning
confidence: 99%
“…1,5,20,27 On the contrary, hyperhomocysteinemia and antiphospholipid antibodies are accepted as risk factors for AT. 20,2730…”
Section: Discussionmentioning
confidence: 99%
“…In regard to thrombosis following the diagnosis of OAPS the evidence is discordant between studies, as some suggest that the rate of thrombosis is low ( Alijotas-Reig et al, 2015 ; Jiang et al, 2021 ), while others documented a high risk despite preventive therapy ( Lefèvre et al, 2011 ; Drozdinsky et al, 2017 ). One such example is derived from The APS ACTION cohort in which the risk of thrombosis amounted to 60% among OAPS patient ( de Jesús et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Different situations are encountered which feed the heterogeneity of situations, fears and care: pregnant women with no known historical positivity for aPL Abs but new evidence of positive aPL Abs, women with a known asymptomatic chronic carriage of aPL Abs but no constituted APS, those with a previous diagnosis of pure thrombotic APS (tAPS), of pure obstetric APS (oAPS), or of thrombotic and oAPS (mixed APS). Despite generally similar autoantibodies and biochemical profiles, patients with tAPS have a higher risk of recurrent thrombosis than patients with oAPS, 17 supporting distinct mechanisms of pathogenesis. 18 Large scale histological studies have shown that neither thrombosis nor infarction is common in APS placentae.…”
mentioning
confidence: 94%